Strategies of transition towards a more sustainable food model Contribution of the Malagueña goat - Morales E.; Micheo J.M.; Antúnez I.; Grande D.; Ruíz F.A.; Mena Y. (Innovation for sustainability in sheep and goats, 2019)
In the last decade the goat industry of Malaga (Spain) had a remarkable development which was accompanied by a progressive intensification of the production system. A significant percentage of the milk and goat products obtained in the province of Malaga are destined for processing and marketing outside the territory. This constitutes one of the main weaknesses of goat production in this area. As consequence, farmers do not participate of the added value obtained from processed products. Likewise, the Andalusian consumers have little knowledge of goat activity and they consume few local goat products. These circumstances lead a progressive abandonment of traditional livestock in spite of its importance from an economic, social and environmental point of view. Aware of this situation, the Malagueña Goat Breeders Association is carrying out a threeyear project funded by the Daniel & Nina Carasso Foundation. The programmed actions are grouped around four types of activities: i) to develop an own offer of local and quality products by the goat farmers; ii) creation of a stable tourist services structure; iii) to promote the transition to more sustainable production models such as ecological certification and iv) carried out transversal actions to divulge the diverse activities of the project. The most outstanding actions carried out so far include the opening of the Multifunctional Center of the Malagueña Goat, the approximation level evaluation of the Malagueña goat farms to the organic model, and diverse informative activities such as publications, TV programs and congress presentations.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)